Electrical conductivity and accelerated aging in amaranth (Amaranthus crueentus L.) seeds - Thaís D’Avila Rosa (Journal of Seed Science)
Abstract: The objective of this study was to determine adequate conditions of water volume, seed quantity and immersion period to perform the electrical conductivity test, and to analyze the parameters of the accelerated aging test and its correlation with the the physiological potential of amaranth seeds. Five lots of amaranth seeds (Amaranthus cruentus), cultivar BRS Alegria, were used. The initial evaluation of the quality of these lots comprehended the following tests: water content, germination, first germination count, accelerated aging (traditional method, and modified versions, using unsaturated and saturated saline solution for the periods of 24, 48 and 72 h), electrical conductivity in different periods (2, 4, 6, 8 and 24 h), different quantities of water (25, 50 and 75 mL), different seed quantities (100 and 150), and field emergence. It could be concluded that the accelerated aging test at 41 °C, for 72 h, using unsaturated NaCl solution was efficient in the classification of amaranth seed lots in levels of vigor. The electrical conductivity test performed for 8 hours with 25 mL of water and 100 seeds was efficient in the classification of amaranth seeds as to their physiological potential.